1997
DOI: 10.2307/3433376
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormones, Bone Mineral Density, and Risk of Breast Cancer

Abstract: 593-599 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Our findings confirm that a high bone mass may be an indicating risk factor for breast cancer 10,[21][22][23][24][25] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings confirm that a high bone mass may be an indicating risk factor for breast cancer 10,[21][22][23][24][25] .…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that these reproductive factors contribute to the higher BMD in women with breast cancer compared to healthy controls. In addition to these results, studies have shown a 52% reduction in breast cancer risk in women with osteoporosis-related vertebral fractures 10 . Prospective analysis of more than 90 000 postmenopausal women enrolled in the Women's Health Initiative observational study revealed a 31% increase in the risk of fracture in breast cancer survivors 11 .…”
Section: Introductionmentioning
confidence: 97%
“…The mechanism underlying this association is unclear, but it has been hypothesized that higher BMD is a time-integrated marker of higher circulating estrogens and androgens that are positively associated with risk (56). It was hypothesized that the DISC intervention group participants would have lower BMDs compared to the usual care group participants.…”
Section: Discussionmentioning
confidence: 99%
“…The next significant reproductive event is the first full-term pregnancy. Risk estimates for breast cancer are significantly reduced for women who give birth before age 25 [Vorherr, 1987;Russo and Russo, 1994;Brinton et al, 1995;Lipworth, 1995;Weiss et al, 1996;Kuller et al, 1997;Tavani et al, 1997], but elevated in those who have their first child after age 30 [Murrell, 1991]. Perimenopause begins at around 35 years of age with a gradual reduction in estrogen levels until the ovaries cease production, signaling menopause.…”
Section: Agementioning
confidence: 99%